Pemanfaatan Endorse dan Hashtag untuk Pemasaran Produk Menggunakan Instagram pada UMKM di Kecamatan Patuk Kabupaten Gunung Kidul - Retnowati, Nurcahyani Dewi; Indrianingsih, Yuliani; Honggowibowo, Anton Setiawan (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2020)
Micro, Small and Medium Enterprises (MSMEs) are businesses that develop in the community and can increase Indonesia's economic growth. These MSMEs are spread in many areas, including the Patuk District in Gunung Kidul Regency and are engaged in products and services. Until now, the marketing of products carried out by SMEs in Patuk District is conventional marketing, which is marketing products through relationships within the business community. So it is very important to increase product marketing by using online marketing based on social media, one of which is using Instagram. The use of Instagram as a marketing medium also requires the use of endorse and hashtags to further optimize marketing. Therefore, SMEs in Patuk Subdistrict need training on how to use Instagram as a marketing strategy, especially on how to utilize endorse and hashtag so that marketing is expected to be more optimal and targeted. To meet the needs of partners (UMKM actors), mentoring is used in the use of endorse and hashtags on Instagram social media as a product marketing medium by implementing community service, which is a lecturer in the Informatics Engineering Study Program at Adisutjipto College of Technology. This assistance can improve the ability of SMEs in Patuk District to utilize endorse and hashtag using Instagram as an effort to improve product marketing. The results of the community service activities show that 10% of community service participants have not been able to use Instagram optimally because they only come on the first day, 20% of community service participants have been able to use Instsgram well but have not been optimal in using endorse and hashtag, and 70% of community service participants have very optimal using Instagram and utilizing endorse and hashtag.